Revenge in rubies : a Harriet Gordon mystery - Stuart, A. M., 1959- (Stuart, A. M., 1959- Harriet Gordon mystery., 2020)
"When Harriet Gordon receives a note from a friend about a tragic death, she and Inspector Curran are thrust into a web of family secrets that threatens to destroy them both in this all-new mystery from the author of Singapore Sapphire. Inspector Curran arrives at the scene of a brutal murder. Sylvie Nolan, the new and much younger wife of the lieutenant colonel John Nolan, a commanding officer currently posted to Singapore, has been bludgeoned to death in a locked room. A heavy silver candlestick and journal are missing from the victim's room. Her husband had been attending a dinner in the officers' mess and slept in a separate bedroom, so her body was not discovered until morning. Harriet Gordon and her brother, Julian, arrive to comfort Pris, the lieutenant's sister. Both Harriet and Curran are baffled by the crime scene and immediately turn to the victim's new family for clues. But Sylvie's distinguished father has a military history with Curran and is doing all he can to get him off the case. Things are further complicated when Curran comes down with malaria, leaving Harriet to detangle the complicated and treacherous Nolan family tree alone. What she uncovers puts both her life and Curran's in grave danger. . "--